Quantification And Optimization of Pavement Design Using Life Cycle Assessment - Nurul Afifah Abd. Khalil (School of Environmental Engineering, Universiti Malaysia Perlis, 2016)
This research aims to explore the complex relationship between pavements and the environment. The objective is to provide insights into appropriate issues and clarify opportunities to increase the environmental performance of this infrastructure system. This is accomplished through two primary objectives to quantify significant environmental impact across the life cycle of pavement construction. To optimize environmental impact of pavement design using life cycle assessment.